Acting sub specie boni - Mayr, Erasmus (Philosophical Explorations, 2017)

Adaptive abilities - Mayr, Erasmus; Vetter, Barbara (Nous-Supplement: Philosophical Issues, 2023)
Abilities, in contrast to mere dispositions, propensities, or tendencies, abilities seem to be features of agents that put the agent herself in control. But what is the distinguishing feature of abilities vis-à-vis other kinds of powers? Our aim in this paper is to point, in answer to this question, to a crucial feature of abilities that existing accounts have tended to neglect: their adaptivity. Adaptivity is a feature of how abilities are exercised. The main reason for its relative neglect has been that most extant accounts have focused solely on whether abilities are exercised successfully in certain possible situations and have mostly understood the exercise of an ability in terms of complete successful performance. We begin by pointing out two aspects of abilities with regard to which current accounts seem (at best) incomplete: control and exercise. We then introduce adaptivity as we understand it, and end by putting it to work in developing a fuller understanding of abilities that does better than current accounts.
CRIS-Team Scopus Importer:2023-09-15

A Kantian Plea for Virtues? - Mayr, Erasmus (Aristotelian Ethics in Contemporary Perspective, 2013)

Akteurskausalität und das Datiertheitsproblem - Mayr, Erasmus (Erwägen Wissen Ethik, 2009)

Alternative Possibilities and Asymmetry - Mayr, Erasmus (Synthese, 2017)

"An erring conscience is an absurdity" The later Kant on certainty, moral judgment and the infallibility of conscience - Knappik, Franz; Mayr, Erasmus (Archiv fur Geschichte der Philosophie, 2019)
This article explores Kant's view, found in several passages in his late writings on moral philosophy, that the verdicts of conscience are infallible. We argue that Kant's infallibility claim must be seen in the context of a major shift in Kant's views on conscience that took place around 1790 and that has not yet been sufficiently appreciated in the literature. This shift led Kant to treat conscience as an exclusively second-order capacity which does not directly evaluate actions, but one's first-order moral judgments and deliberation. On the basis of this novel interpretation, we develop a new defence of Kant's infallibility claim that draws on Kant's account of the characteristic features of specifically moral judgments.
CRIS-Team WoS Importer:2019-03-20

Anscombe and Intentional Agency Incompatibilism (for human and animal agents) - Mayr, Erasmus (Synthese, 2022)
In "Causality and Determination", Anscombe stressed that, in her view, physical determinism and free action were incompatible. As the relevant passage suggests, her espousal of incompatibilism was not merely due to specific features of human 'ethical' freedom, but (also) due to general features of agency, intentionality, and voluntariness. For Anscombe went on to tentatively suggest that lack of physical determination was required for the intentional conduct of animals we would not classify as ,free', too. In this paper, I examine three different lines of argument to establish Anscombe's latter suggestion, which are based on general considerations about the causal efficacy of psychological-agential phenomena, the nature of agency, and the specific features of intentional agency. I start with Anscombe's own claim from "The Causation of Action" that microphysical determinism would make psychological and personal phenomena epiphenomenal, before I turn to the view of 'Agency Incompatibilism', that genuine agency requires the absence of antecedent necessitation, and, lastly, to concerns about some crucial features of intentional agency which we find in both human and animal agents.
CRIS-Team WoS Importer:2022-06-17
Keywords: Elizabeth Anscombe; Mechanism and microphysical determinism; Agency Incompatibilism; Helen Steward; Active Powers and antecedent determination; Practical deliberation and determinism

Anton Leist (Hg.), Action in Context - Mayr, Erasmus (2010)

Blame for constitutivists: Kantian constitutivism and the victim’s special standing to complain - Mayr, Erasmus (Philosophical Explorations, 2019)
Constitutivists about moral norms are often suspected of providing an overly “self-centered” account of morality which does not take seriously enough morality’s interpersonal nature. This worry seems particularly pressing in the light of recent debates about the relational character of many moral norms. In this paper, I discuss one aspect of this worry, which concerns the special standing to complain which the victims of wrongdoing have. I argue that, contrary to appearances, Kantian constitutivism can explain this latter feature, since there is a special need for remedying the denial of equal moral standing of the victim and the impairment of the victim’s agency which any wrongdoing involves.
CRIS-Team Scopus Importer:2019-05-02
Keywords: constitutivism; directed moral duties; equal moral standing; Korsgaard; positionality of complaint; role of the victim of wrongdoing

Breve introduzione alla metafisica - Marmodoro, Anna; Mayr, Erasmus (Carocci, 2017)

Comment on The Normativity of Rationality Kommentar zu the normativity of rationality - Mayr, Erasmus (Zeitschrift für Philosophische Forschung, 2017)
CRIS-Team Scopus Importer:2023-03-21

Fiktionale Terme - Mayr, Erasmus (Philosophisches Jahrbuch, 2003)

Freedom of the Will and Rational Abilities - Mayr, Erasmus (Powers, Time and Free Will, 2022)
Since the 1990s, agential capacities and abilities have played an increasingly prominent role in the debate about free will, especially among compatibilists. But it is still not fully clear what precisely compatibilists will gain by relying on capacities and abilities. In this paper, I try to argue that at least for compatibilists of a certain stripe an appeal to abilities is of significant use. These are compatibilists who try to argue for the compatibility of agential freedom and microphysical determinism by distinguishing between different, mutually irreducible levels of explanation (as, e.g., Christian List has recently done). An abilities account of free will provides the grounds for a much-needed principled argument why we can and should disregard certain microphysical features when providing the kind of explanation which is the primary and salient one for explaining intentional actions.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Abilities; Christian list; Compatibilism; Free will; Levels of explanation; Microphysical determinism

Gewissen und Gewissenhaftigkeit beim späten Kant - Mayr, Erasmus; Knappik, Franz (Kant und die Philosophie in weltbürgerlicher Absicht. Akten des XI. Kant-Kongresses, 2013)

Gibt es moralische Bedingungen für normative Gründe? - Mayr, Erasmus; Ammereller, Erich (Normativität, Geltung und Verpflichtung, 2011)

Grenzen des weichen Paternalismus II - Zwischen Harm-Principle und Unvertretbarkeit - Mayr, Erasmus (Grenzen des Paternalismus, 2009)

Hart, Punishment, and Excusing Conditions - Mayr, Erasmus (H.L.A. Hart on Responsibility, 2014)

Informed consent, Patientenautonomie und die Technisierung der Medizin - Mayr, Erasmus (Medizinphilosophie oder philosophische Medizin? Philosophisch-ethische Beiträge zu Herausforderungen technisierter Medizin, 2013)

Instrumentalism and Human Rights: A Response to Buchanan and Sreenivasan - Mayr, Erasmus (Human Rights, Moral or Political?, 2018)

International Criminal Law, Causation, and Responsibility - Mayr, Erasmus (International Criminal Law Review, 2014)

Joseph Raz - Mayr, Erasmus (Philosophie der Gegenwart in Einzeldarstellungen, 2007)

Joseph Raz on responsibility and secure competence - Mayr, Erasmus (Jurisprudence, 2024)
In the last two chapters of his book ‘From Normativity to Responsibility’, Joseph Raz developed, in outline, an intriguing account of responsibility, which is based on what he called the Rational Functioning Principle and on the idea of a domain of secure competence. With these two ideas, Raz argued, we could best delimit the scope of ‘responsibility’ in the sense of something ‘being to one’s credit or discredit as a rational agent’. In the following, I will argue that, while identifying some crucial aspects of our being agents ‘in the world’, Raz’s account does not fully capture the extent of the kind of responsibility he was interested in. In particular, unintentional failures that are due to the malfunctioning of capacities which are too unreliable to count as secure competences may well fall within the scope of responsibility thus understood. I will suggest Raz’s account should be supplemented by considerations drawn from ‘quality of will’ approaches, which can (inter alia) deal better with such cases.
CRIS-Team Scopus Importer:2024-04-19
Keywords: Joseph Raz; quality of will accounts of responsibility; responsibility for unintentional failures; skill-blame

Juristische Normen, Interpretationen und Bedeutungsskepsis - Mayr, Erasmus (Sprache - Recht - Gesellschaft, 2012)

Kant and Hegel on purposive action - Laitinen, Arto; Mayr, Erasmus; Sandis, Constantine (Philosophical Explorations, 2018)
This essay discusses Kant and Hegel’s philosophies of action and the place of action within the general structure of their practical philosophy. We begin by briefly noting a few things that both unite and distinguish the two philosophers. In the sections that follow, we consider these and their corollaries in more detail. In so doing, we map their differences against those suggested by more standard readings that treat their accounts of action as less central to their practical philosophy. Section 2 discusses some central Kantian concepts (Freedom, Willkür, Wille, and Moral Law). In Section 3, we take a closer look at the distinction between internal and external action, as found in Kant’s philosophy of morality and legality. In Section 4, we turn to Hegel and his distinctions between abstract right (legality), morality, and ethical life, as well as the location of his account of action within his overall theory of morality. We discuss the distinction between Handlung and Tat, and non-imputable consequences. The overall aims of our essay are to shed light on some puzzles in Kant and Hegel’s conceptions and to examine where their exact disputes lie without taking a stand on which philosophy is ultimately the most satisfactory.
CRIS-Team Scopus Importer:2023-03-21
Keywords: action; ethics; freedom; Handlung; Hegel; Kant; moral law; Tat; will; Wille; Willkür

Kantian benevolence - Mayr, Erasmus (Proceedings of the Aristotelean Society, 2018)
Kantians may be unable to derive all of benevolence from reverence for rational agency, but the remaining lacuna is not as extensive as Arpaly thinks. For while we should take seriously Kantian worries about separating benevolence from reverence, a considerable part of benevolence can be explained in terms of reverence for rational agency on a plausible intepretation of the latter. Furthermore, Kantians have an irreducible role for benevolence within their ethics, which is different from the role of a self-standing virtue.
CRIS-Team Scopus Importer:2023-03-21

Kausalität und Vermögen - Mayr, Erasmus (Vermögen und Handlung, 2014)

Lucy O'Brien and Mathew Soteriou (eds.), Mental Actions - Mayr, Erasmus (2012)

Marco Iorio, Regel und Grund - Mayr, Erasmus (2012)

Moralismus und die Zuständigkeit für moralische Vorwürfe - Mayr, Erasmus (Kritik des Moralismus, 2020)

Motivation - Mayr, Erasmus (Handbuch Handlungstheorie. Grundlagen, Kontexte, Perspektiven., 2016)

Neo-Aristotelismus, Identitätstheorie und mentale Versursachung - Mayr, Erasmus (Philosophisches Jahrbuch, 2013)

Normativität: Geltung und Verpflichtung. Festschrift für Wilhelm Vossenkuhl - Mayr, Erasmus; Sellmaier, Stephan (Kohlhammer, 2011)

Personal Identity and the Transfer of Commitment - Mayr, Erasmus (The Unity of a Person, 2021)

Powers and Downward Causation - Mayr, Erasmus (Philosophical and Scientific Perspectives on Downward Causation, 2017)

Powers and downward causation - Mayr, Erasmus; Mayr, Erasmus (Philosophical and Scientific Perspectives on Downward Causation, 2017)
CRIS-Team Scopus Importer:2023-03-21

Reasons and Causes: Do Dispositions Help Us Resolve the Old Debate? - Mayr, Erasmus (Jurisprudence, 2016)

Roger Teichmann, Nature, Reason and the Good Life: Ethics for Human Beings - Mayr, Erasmus (2012)

The action-guidingness of rational principles and the problem of our own imperfections - Mayr, Erasmus (Philosophical Inquiries, 2023)
The following comment discusses the supposedly action-guiding role of rational principles and the question to what extent our imperfections as human agents should influence what these principles are. According to Sergio Tenenbaum, the principles of instrumental rationality (as stated in his theory) are meant to be action-guiding rather than merely evaluative. In the first part of the comment, I look at how this action-guiding role is to be understood, especially when it comes to the pursuit of long-term, indeterminate ends. The second part of the comment raises the question of whether the principles included in Tenenbaum’s Extended Theory of Rationality should be supplemented by principles for dealing with our own imperfections. I consider two possible sources for such further prin-ciples: the risk that we will behave irrationally later on and uncertainty about the effective-ness of the means we take.
CRIS-Team Scopus Importer:2023-02-24
Keywords: acting under uncertainty; action-guidingness; extended actions; indeterminate ends; procrastination

The Political and Moral conceptions of Human Rights - a mixed Account - Mayr, Erasmus (The Philosophy of Human Rights. Contemporary Controversies, 2012)

The Problem of Consequential Waywardness: Between Internalism and Externalism about Intentional Agency - Mayr, Erasmus (Causation and Responsibility: Critical Essays, 2013)

Understanding Human Agency - A summary - Mayr, Erasmus (Zeitschrift für Philosophische Forschung, 2013)
CRIS-Team Scopus Importer:2023-03-21

Understanding Human Agency - Mayr, Erasmus (Oxford University Press, 2011)

Understanding Human Agency - Précis - Mayr, Erasmus (Zeitschrift für Philosophische Forschung, 2013)

Understanding Human Agency - Replik - Mayr, Erasmus (Zeitschrift für Philosophische Forschung, 2013)

Unwitting Omissions, Mistakes and Responsibility - Mayr, Erasmus (Agency, Negligence and Responsibility, 2021)

Varieties of constitutivism - Haase, Matthias; Mayr, Erasmus (Philosophical Explorations, 2019)
CRIS-Team Scopus Importer:2019-05-28

Was ist und zu welchem Zweck betreibt man Wissenschaftsreflexion? - Jungert, Michael; Frewer, Andreas; Mayr, Erasmus (Wissenschaftsreflexion. Interdisziplinäre Perspektiven zwischen Philosophie und Praxis, 2020)
Keywords: Wissenschaftsreflexion; Wissenschaftsphilosophie; Wissenschaftstheorie; Wissenschaft und Gesellschaft

Willensfreiheit - Mayr, Erasmus (Handbuch Metaphysik, 2017)

Wissenschaftsreflexion. Interdisziplinäre Perspektiven zwischen Philosophie und Praxis - Jungert, Michael; Frewer, Andreas; Mayr, Erasmus (Mentis/Brill, 2020)
Wissenschaftsreflexion: eine neue interdisziplinäre Perspektive auf die Geschichte, Theorie und Ethik der Wissenschaften sowie auf die praktischen Auswirkungen von wissenschaftlicher Forschung und Erkenntnis. Die Wissenschaften sehen sich gegenwärtig mit Blick auf ihre Geltungs- und Wahrheitsansprüche, ihre Vertrauenswürdigkeit und ihre Rolle in der Gesellschaft vor grundlegende Herausforderungen gestellt. Die Diskussionen betreffen dabei so unterschiedliche Themen wie Unsicherheit, Scheitern oder „Fake News“ in den Wissenschaften, Klimawandel, Gentechnik, Impfungen und Alternativmedizin oder Evolutionstheorien. Nur eine interdisziplinär angelegte Reflexion über die Rolle der Wissenschaften, ihren Erkenntnisanspruch und ihre Methoden wird diesen neuen Herausforderungen gerecht. Mit dem vorliegenden Band wird erstmals der Begriff der Wissenschaftsreflexion differenziert eingeführt und interdisziplinär diskutiert. Der Band umfasst vielfältige Beiträge zu Grundlagen- und Anwendungsfragen aus unterschiedlichen Disziplinen, die gemeinsam eine pluralistische Perspektive eröffnen und konkrete Lösungsmöglichkeiten aufzeigen.
Keywords: Wissenschaftsreflexion; Wissenschaftsgeschichte; Wissenschaftsethik; Wissenschaft und Gesellschaft; Wissenschaft und Paxis; Wissenschaftsphilosophie; Wissenschaftstheorie; Vertrauen in die Wissenschaft; Wissenschaftsskepsis; Wissenschaftskritik